PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN PORSI KEPEMILIKAN PUBLIK, TERHADAP ENVIRONTMENTAL DISCLOSURE (Studi pada Perusahaan Logam dan Mineral Lainnya yang Terdaftar di Bursa Efek Indonesia) - Ijma, Ijma (Katalogis, 2018)
The purpose of this research is to know the influence of firm size, profitability and public ownership portion on environmental disclosure partially and simultaneously. The method used in this research is quantitative approach with regression analysis. The sample is chosen by purposive sampling technique. There is eight firms as sample. Analysis unit of this research is annual report of mineral and metal industries of 2011-2015 period, that are 40 annual report. The result shows that the firm size, profitability and public ownership portion have significant effect on environmental disclosure simultaneously. Partially, the firm size and public ownership portion have significant effect on environmental disclosure. But, profitability doesn’t have significant effect on environmental disclosure. Based on these results, the big firm and more public ownership portion disclose more completely about environmental responsibility on the firm annual report. But, the level of firm profitability doesn’t affect the firm environmental disclosure.